A survey on Approaches Used for Efficient Workload Management in Geo-Distributed Data Centres - Ramya, D; Deepa, J; N.Karthikayan, P (International Journal of Engineering and Technology, 2018)
A geographically distributed Data center assures Globalization of data and also security for the organizations. The principles for Disaster recovery is also taken into consideration. The above aspects drive business opportunities to companies that own many sites and Cloud Infrastructures with multiple owners.Â The data centers store very critical and confidential documents that multiple organizations share in the cloud infrastructure. Previously different servers with different Operating systems and software applications were used. As it was difficult to maintain, Servers are consolidated which allows sharing of resources at low of cost maintenance [7]. The availability of documents should be increased and down time should be reduced. Thus workload management becomes a challenging among the data centers distributed geographically. In this paper we focus on different approaches used for workload management in Geo-distributed data centers. The algorithms used and also the challenges involved in different approaches are discussedÂ